Women Undergoing Donor IVF Treatment: The Moderating Role of Economic Independence in Isfahan - Heydar Zafari; Aliasghar Mohajerani; Sayed Naser Hejazi (جامعه شناسی کاربردی)
IntroductionInfertility is a significant social concern worldwide, including in Iran. In many societies, particularly our own, femininity is often defined through motherhood, which is frequently viewed as the primary means for women to enhance their status within the family and society (Hasanpoor-Azghady et al., 2019). The ability to have children is perceived as a vital individual, social, and cultural value. In developing countries, the negative effects of infertility are often more pronounced due to various social, cultural, and economic factors, leading to considerable social pressure on couples (Ebrahimzadeh Zagami et al., 2021). This study aimed to sociologically analyze the impact of social stigma on relationship quality among infertile men and women undergoing donor IVF treatment with a particular focus on the moderating role of women's economic independence within the family. Specifically, the research examined how social stigma influenced the quality of family and social relationships for both men and women undergoing donor IVF treatment. Additionally, it assessed the extent to which women's economic independence moderated the effect of social stigma on these relationships.  Materials & MethodsThis research employed a quantitative, cross-sectional design, distinguishing it from longitudinal studies. The unit of analysis was micro-level, focusing on individual families (husband and wife). As such, the study was categorized as survey research, falling under non-experimental methods. The statistical population included all infertile men and women, who visited the Isfahan Fertility and Infertility Center and the Pouyesh Fertility Center for treatment during 2022 and 2023. The sample size was estimated using SPSS Sample Power software, resulting in a minimum of 140 sample units based on specific criteria. Ultimately, 147 samples were analyzed to test the hypotheses. Data collection was conducted using a questionnaire that measured the quality of family relationships, the quality of social relationships, and the social stigma associated with infertility, employing the instruments adopted by Golombok-Rust (1985), Pierce et al. (1991), and Younesi et al. (2005), respectively. Additionally, women's economic independence was assessed based on their approximate income levels. To evaluate the validity and reliability of the measurement tools, factor validity techniques were applied for reflective measures, while face validity was used for formative measures. The results indicated that all tools suitable for this technique demonstrated factor validity. Reliability analysis showed that all reflective scales and subscales exhibited internal consistency with Cronbach's alpha coefficients exceeding 0.90 or being very close to that threshold. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach, utilizing SmartPLS4 software. Discussion of Results & ConclusionThe descriptive analysis of the research variables revealed that the infertile men and women rated the quality of their family relationships with their spouses as good to excellent, while their social relationships were perceived as average. Regarding social stigma, the analysis indicated that, on average, the participants experienced social stigma although its severity was below the average threshold. Hypothesis testing demonstrated that social stigma negatively impacted both the family and social relationships of couples undergoing donor IVF treatment. However, the moderating role of women's economic independence was not supported by the findings. Overall, the results suggested that social stigma adversely affected the family and social dynamics of couples undergoing donor IVF treatment, regardless of the woman’s economic independence. The decline in the quality of family and social relationships among infertile couples due to social stigma is a complex and multifaceted issue that requires careful attention and comprehensive support. To aid these couples, the society can foster a more supportive environment by increasing public awareness of infertility and addressing the negative stigmas associated with it. This awareness can be promoted through various media, including television, radio, and social networks, as well as through workshops and seminars. Additionally, providing counseling services and establishing support groups for infertile couples can be beneficial. Furthermore, developing and implementing supportive legislation—such as financial assistance, access to treatment services, and protections for the rights of infertile couples in the workplace—can help them navigate the challenges of infertility and successfully undergo treatment.